Digital Transformation and Informal Work: A Narrative Review of Platform Economies in the Global South - Andika, Cruift (Yayasan Sinergi Kawula Muda, 2025)
The rise of digital platforms has significantly transformed informal labor markets in developing economies, offering both opportunities and challenges. This narrative review synthesizes current research on the economic impacts of digital platforms, focusing on job creation, precarity, gender and migrant dynamics, and regional disparities. Literature was collected from Scopus, Web of Science, and Google Scholar using targeted keywords, emphasizing peer-reviewed studies published between 2010 and 2024. Findings indicate that digital platforms contribute significantly to employment generation and income growth, though challenges persist such as income instability, lack of social protection, and algorithmic bias. While digital platforms can drive inclusive growth, their transformative potential depends on regulatory frameworks, social protections, and equitable digital inclusion policies.